Sosial Dan Kepribadian Terhadap Keputusan Mahasiswa Pemilihan Program Studi Manajemen - Sandra Oktaviana Pinaraswati (BALANCE: Economic, Business, Management and Accounting Journal, 2020)
The purpose of this study is to examine and analyze: The influence of social and personality factors on students' decisions in choosing a Management study program. The research method used is explanatory research that is research that explains the causality relationship between several variables through hypothesis testing. Data collection techniques using a questionnaire or questionnaire in the form of a Likert scale. The research respondents were undergraduate students of 2017 management study program at Higher Education in Surabaya with a total sample of 281 students. The analytical model in this study is to use multiple linear regression analysis. The results showed the R Square coefficient of 0.504 means that the Student Decision variable can be explained by Social and Personality variables, by 50.4%. While the remaining 49.6% can be explained by other variables not examined by this study. Simultaneous testing shows that the independent variables namely Social and Personality together affect the Student's Decision. This is indicated by the F count of 141,161. The partial test of research variables shows that the independent variables, namely Social and Personality, influence the dependent variable, namely Student Decisions.Keywords                   : Social, Personality, Student Decisionss